Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Keputusan Pembelian Konsumen TikTok Shop - Amalia, Fanny; Febianti, Yopi Nisa; Wiradinata, Rochanda (Jambura Economic Education Journal, 2026)
This study aims to determine the influence of the marketing mix and the most dominant influence of the marketing mix on the purchasing decisions of TikTok Shop consumers. This study used quantitative methods with a survey approach, and data collection using questionnaires. The simple random sampling technique was used to select respondents who produced 73 students of the Faculty of Education and Science UGJ Cirebon. Testing and data analysis is carried out using the help of SPSS Software 25.0 for windows. The conclusion of this study is that there is a positive and insignificant influence of product and price on consumer purchasing decisions, while place and promotion have a positive and significant effect on purchasing decisions, then promotion has the most dominant influence on TikTok Shop purchase decisions in FPS UGJ Cirebon students.